Incidencia de apendicitis en niños de 6 a 15 años en el hospital general Teófilo Dávila enero a abril 2022 - Segura García, Dany Nallith; Vásquez Mendoza, Erika Solange; Mora Veintimilla, Gladis (My University, 2022)
introduction: Appendicitis is currently considered the most common emergency worldwide due to its high incidence of cases in any corner of the world. In Ecuador, acute appendicitis in paediatric patients is one of the main causes of surgical admissions. Data published by INEC indicate that for every 10,000 Ecuadorians, 22.97 are diagnosed with appendicitis. Objective: To identify the degree of incidence of appendicitis in children from 6 to 15 years of age treated at the General Hospital Teófilo Dávila Methodology: The present scientific work is of transversal type due to the fact that the time to perform it tube a determined lapse, it was also descriptive since a systematic search of scientific information was performed in high impact journals such as: SCIELO, LATINDEX, SCOPUS, PUBMED, SCIENCEDIRECT, DIALNET, the systematization of the information was performed by means of the statistical system SPSS V26. Results: In this research topic, the degree of incidence presented in children from 6 to 15 years old with appendicitis attended at the General Hospital Teófilo Dávila was identified, in which aspects that coincide with the consulted bibliography could be evidenced such as, the highest incidence of appendicitis in children from 11 to 15 years old in an amount of 13 cases while from 6 to 10 years old we can only evidence 7 cases. Taking into account that our population is composed of 24 cases studied
Introducción: La apendicitis en la actualidad es considerada la emergencia más común a nivel mundial debido a su gran incidencia de casos en cualquier rincón del mundo. En Ecuador la apendicitis aguda en pacientes pediatras es una de las principales causas de ingresos quirúrgicos, datos publicados por el INEC indican que por cada 10.000 ecuatorianos 22,97 son diagnosticados con apendicitis. Objetivo: Identificar el grado de incidencia que se presenta en niños de 6 a 15 años con apendicitis atendidos en el Hospital General Teófilo Dávila Metodología: El presente trabajo científico es de tipo transversal debido a que el tiempo para realizarlo hubo un lapso determinado, también fue descriptivo ya que se realizó búsqueda sistemática de información científica en revistas de alto impacto como: SCIELO, LATINDEX, SCOPUS, PUBMED, SCIENCEDIRECT, DIALNET, la sistematización de la información se la realizó mediante el sistema estadístico SPSS V26. Resultados: En este tema de investigación se identificó el grado de incidencia que se presenta en niños de 6 a 15 años con apendicitis atendidos en el Hospital General Teófilo Dávila, en el cual se pudieron evidenciar aspectos que coinciden con la bibliografía consultada tales como, la mayor incidencia de apendicitis en niños de 11 a 15 años en una cantidad de 13 casos mientras que de 6 a 10 años solo podemos evidenciar 7 casos esto al tener en cuenta que nuestra población está compuesta por 24 casos estudiados.
Keywords: APENDICITIS; PACIENTE PEDIÁTRICO; INCIDENCIA.